Effect Of Kolawole’s Problem-Solving Teaching Strategy On The Academic Performance Of Secondary School Students In Mathematics In Nigeria - S. O. , Olofin; Kolawole, E. B. (Advances in Social Sciences Research Journal, 2020)
The study examined the effects of Kolawole’s Problem Solving (KPS) teaching strategy on the academic performance of secondary school students in Mathematics in Nigeria. Specifically, the study was designed to ascertain which of the strategies (KPS or conventional) would be the more effective in the teaching of Mathematics. The study also investigated the difference in the academic performance of students exposed to KPS strategy in three geo-political zones of Nigeria. Quasi – experimental pre-test and post-test two group design (one experimental group and one control group) was used in the study. The sample consisted of 562 S.S.S. 2 students drawn from eighteen public secondary schools in three geo-political zones of Nigeria. The sample was selected using multistage sampling procedure. Performance Test in Mathematics (PTM) was used to collect relevant data for this study. The data were analyzed using descriptive and inferential statistics at 0.05 level of significance. The findings of the study showed that the two groups (KPS and Conventional) were homogeneous at the commencement of the experiment. Also, there was significant difference in the post-test mean score of students exposed to KPS and conventional strategies in favour of students exposed to KPS strategy. Furthermore, there was difference in students’ performance in Mathematics when exposed to KPS based on their geo-political zones. Based on the findings of the study, it was recommended among others that the use of KPS strategy should be encouraged in Mathematics class in secondary schools so as to enhance better academic performance of students in Mathematics.